KETIDAKHARMONISAN KELUARGA TERHADAP TINDAKAN SOSIAL DAN SPIRITUAL REMAJA DI YOUTH GBI EBEN HAEZER - Ibnu Salman; Onnie Lumintang; Yada Putra Gratia; Sewi Anastasya Simamora (Diegesis : Jurnal Teologi, 2021)
The problem of juveniles today is increasingly troubling the community, especially in a cosmopolitan city like Jakarta. Developed countries, as well as developing countries, also feel uneasy because juvenile delinquency is increasingly occurring which has a negative impact on people's social life. Call it the problem of rebellion against parents, free sex, smoking, and intoxicating alcoholic drinks. This problem also extends to the youth of the church who live together with society at large. The root of this problem is the wholeness and harmony of the family in educating children according to God's Word. This study aims to examine the effect of disharmony in the family on the social and spiritual lives of young people. The method used is quantitative with the Y variable being the social and spiritual life of the youth of the Masterplan Youth GBI Eben Heazer. The results showed that the effect of family disharmony was in the very low category. This means that family disharmony does not have a big influence on the social and spiritual life of adolescents. Juvenile delinquency that occurs can be influenced by other factors such as economic conditions, the environment or it can be from individual factors themselves.